2021
DOI: 10.1039/d1ta05000a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low doping on the improvement of cathode materials Na3+xV2−xMx(PO4)3 (M = Co2+, Cu2+; x = 0.01–0.05) for SIBs

Abstract: In this work, we demonstrate the advantages of low doping in relation to the electrochemical properties of the NVP cathode for use in SIBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Significantly, the optimized KC0.05/CNTs obviously deliver a high and stable capacity at ultrahigh rates, suggesting that it possesses an enhanced structural stability and an efficient electronic conductive network. Besides, we also compare the comprehensive performance containing initial capacity, cyclic property, and retention ratio of KC0.05/CNTs with other modified NVP materials reported previously. , As shown in Figure h, it is clearly that KC0.05/CNTs exhibits a higher comprehensive performance. Above all, the greatly improved electrochemical performance demonstrates that the strategy of K/Co co-doping and CNTs enwrapping can strongly enhance the structural stability, expand channels for Na + migration, and establish a perfect conductive network to improve the sodium storage property of NVP system…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Significantly, the optimized KC0.05/CNTs obviously deliver a high and stable capacity at ultrahigh rates, suggesting that it possesses an enhanced structural stability and an efficient electronic conductive network. Besides, we also compare the comprehensive performance containing initial capacity, cyclic property, and retention ratio of KC0.05/CNTs with other modified NVP materials reported previously. , As shown in Figure h, it is clearly that KC0.05/CNTs exhibits a higher comprehensive performance. Above all, the greatly improved electrochemical performance demonstrates that the strategy of K/Co co-doping and CNTs enwrapping can strongly enhance the structural stability, expand channels for Na + migration, and establish a perfect conductive network to improve the sodium storage property of NVP system…”
Section: Resultsmentioning
confidence: 73%
“…Besides, we also compare the comprehensive performance containing initial capacity, cyclic property, and retention ratio of KC0.05/CNTs with other modified NVP materials reported previously. 49,50 As shown in Figure 4h, it is clearly that KC0.05/CNTs exhibits a higher comprehensive performance. Above all, the greatly improved electrochemical performance demonstrates that the strategy of K/Co co-doping and CNTs enwrapping can strongly enhance the structural expand channels for Na + migration, and establish a perfect conductive network to improve the sodium storage property of NVP system Figure 5a depicts the GCD curves of KC0.05/CNTs and NVP within the range in 2.3−4.1 V. The two electrodes both release a long plat at 3.4 V belonging to the V 3+ /V 4+ redox pair and the charge capacity of KC0.05/CNTs (119.4 mA h g −1 ) is greatly more than NVP (87.5 mA h g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the Na 4 Mn 0.9 Ce 0.1 V(PO 4 ) 3 @CeO 2 /C electrode possessed more stable kinetic properties during the cycling test. 64…”
Section: Resultsmentioning
confidence: 99%
“…Notably, phosphate materials, which belong to the polyanion type with strong covalence bindings, have attracted plentiful attention due to their high safety and stability. Na 3 V 2 (PO 4 ) 3 (NVP), the representative phosphate material, has been widely applied as the cathode in SIBs; [25][26][27][28][29][30] it consists of repeated V 2 (PO 4 ) 3 groups, which further form an open 3D NASICON framework with lots of inner channels. Notably, it possesses excellent electrochemical properties with the theoretical potential and capacity values of 3.4 V and 117.6 mA h g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Na 3 V 2 (PO 4 ) 3 (NVP), the representative phosphate material, has been widely applied as the cathode in SIBs; 25–30 it consists of repeated V 2 (PO 4 ) 3 groups, which further form an open 3D NASICON framework with lots of inner channels. Notably, it possesses excellent electrochemical properties with the theoretical potential and capacity values of 3.4 V and 117.6 mA h g −1 .…”
Section: Introductionmentioning
confidence: 99%